Constituents of the rhizome of Curcuma aeruginosa and its DNA fingerprint - Chantana Aromdee,; Senee Polrat,; Preeya Wangsomnuek, (International Journal of Phytomedicine, 2011)
Identity of the rhizhome of Curcuma aeruginosa Roxb. was established by three techniques: (1) the DNA fingerprint, (2) the chemical constituents of its volatile oils by using gas chromatographmass spectrometer, and (3) thin-layer chromatography (TLC) of the methanol extract. These three techniques were used to differentiate C. aeruginosa from its similar species. Result from the polymerase chain reaction (PCR) amplification, different polymorphic bands between the two specimens were found. The relative amounts of camphor, curzerenone and epicurzerenone in the C. aeruginosa rhizome were 16.85, 16.81 and 3.5% of total peak areas, whereas 6.04, 0 and 62.84% of total peak areas were found in the Curcuma sp. The thin-layer chromatogram revealed that Curcuma sp. contained curcumine, whereas only traces were detected in C. aeruginosa.